Dark Lord : The Teenage Years - Lloyd, Dirk (Fictitious character); Thomson, Jamie, 1958- (London : Orchard Books, 2011)
Now acclimated to life as a thirteen-year-old Earthling, Dirk Lloyd has contacted his home in the Darklands but so has his friend Sooz, who is forming her own alliances.
Jamie Thompson is crossed out and replaced with Dirk Lloyd on the t.p.
7.1
5-8.
5-8
Keywords: Magic -- Juvenile fiction; Fantasy; Humorous stories; Magic -- Fiction; Humorous fiction; Magic -- Fiction; Fantastic fiction; Fantastic fiction; Humorous fiction